Functional Preservation and Reorganization of Brain during Motor Imagery in Patients with Incomplete Spinal Cord Injury: A Pilot fMRI Study - Chen, Xin; Wan, Lu; Qin, Wen; Zheng, Weimin; Qi, Zhigang; Chen, Nan; Li, Kuncheng (Frontiers in Human Neuroscience, 2016)
Motor imagery (MI) is a cognitive process involved in mentally rehearsing movement representations, and it has great potential for use in the rehabilitation of motor function in patients with spinal cord injuries. The aim of this study was to explore changes in the brain activation patterns in incomplete spinal cord injury (ISCI) patients during motor execution (ME) and MI tasks, and to thereby explore whether MI shares similar motor-related networks with ME in ISCI patients. Seventeen right-handed ISCI patients with impaired motor function of their right ankles and seventeen age- and gender-matched healthy controls were enrolled in this study. The activation patterns of the ISCI subjects and those of the healthy subjects were compared, both during mental dorsi-plantar ﬂexion of the right ankle (the MI task) and the actual movement of the joint (the ME task). The patients and the healthy controls shared similar activation patterns during the MI or ME tasks. The activation patterns of the MI task between the patients and the healthy controls were more similar than those of the ME task. These findings indicate that the MI network is more functionally preserved than the ME network in ISCI patients. In addition, increased activation in the motor-related regions during ME task, and decreased activation in the parietal regions during both ME and MI tasks, were identified in the ISCI patients compared to the healthy controls, indicating a functional reorganization of these regions after ISCI. The functional preservation and reorganization of the MI network in the ISCI patients suggests a potential role for MI training in motor rehabilitation.